1985
DOI: 10.1159/000233825
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Allergic Histamine Release by Azelastine and Selected Antiallergic Drugs from Rabbit Leukocytes

Abstract: The ability of azelastine to inhibit allergic histamine release from rabbit mixed leukocytes was studied and compared with selected antiallergic drugs. Azelastine, ketotifen, diphenhydramine, theophylline and disodium cromoglycate (DSCG) produced concentration-dependent inhibition of allergic histamine release from rabbit basophils. The concentrations inhibiting histamine release by 50% (IC50; μM)were as follows: azelastine = 4.5; ketotifen = 9.5; diphenhydramine = 18.9; theophylline = 56.9; DSCG = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…Azelastine possesses calm odulin [12] and Ca2+ [15] antagonistic activities. It has also been shown to inhibit the form ation of su peroxide radicals (•O2) [16] as well as allergic and nonallergic histamine secretion [13,17]. It exerts anti inflam m atory activity, i.e., it inhibited an antigen-in duced increase in capillary perm eability in experi mental anim al model systems [9,18].…”
Section: Introductionmentioning
confidence: 99%
“…Azelastine possesses calm odulin [12] and Ca2+ [15] antagonistic activities. It has also been shown to inhibit the form ation of su peroxide radicals (•O2) [16] as well as allergic and nonallergic histamine secretion [13,17]. It exerts anti inflam m atory activity, i.e., it inhibited an antigen-in duced increase in capillary perm eability in experi mental anim al model systems [9,18].…”
Section: Introductionmentioning
confidence: 99%
“…Azelastine [4-(/?-chlorobenzyl)-2-(hexahydro-1 -me thyl-1 H-azepine-4-yl)-l-(2H)-phthalazinone hydro chloride] has been shown to inhibit immunologically and nonimmunologically provoked histamine release from rat peritoneal mast cells [3][4][5][6] and rabbit leuko cytes [7], The drug showed a potent and long-acting antiallergic effect in several animal models of allergic hypersensitivity reactions, such as bronchospasm in guinea pigs [8], passive cutaneous anaphylaxis (PCA) in guinea pigs [3] and rats [3,9], and passive Arthus reactions in guinea pigs [3,10]. It is well established that azelastine has potent histamine HI receptor blocking properties in vitro and in vivo [3,8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that it prevents the synthesis/release of mediators such as histamine (Chand et al, 1985), leukotrienes (Chand et al, 1989;Nishihira et al, 1989), superoxide anions (Busse et al, 1989;Taniguchi & Takanaka, 1989), arachidonic acid (Taniguchi & Takanaka, 1989), and that it antagonizes the effect of some of these mediators on target organs (Rafferty et al, 1989). In addition, Nakamura et al (1988) have shown that azelastine inhibits the release of Ca2+ from intracellular storage sites in guinea-pig peritoneal macrophages stimulated by PAF or by FMLP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Nakamura et al (1988) have shown that azelastine inhibits the release of Ca2+ from intracellular storage sites in guinea-pig peritoneal macrophages stimulated by PAF or by FMLP. Azelastine was also described as an inhibitor of leukocyte (Chand et al, 1985;Taniguchi & Takanaka, 1989;Busse et al, 1989), and platelet functions (Achterrath-Tuckermann et al, 1988). Azelastine is effective in animals (Chand et al, 1986;AchterrathTuckermann et al, 1988), and has been claimed to reduce allergic rhinitis (Meltzer et al, 1988) and asthma Kemp et al, 1987).…”
Section: Discussionmentioning
confidence: 99%